Perform-therapy as a method for restoring identity under conditions of postmodernist fragmentation - Anatoliy A. Grebenyuk (Russian Journal of Education and Psychology, 2025)
Background. The identity crisis caused by the cultural context of postmodernism manifests in fragmentation, ironic detachment, and the loss of the ability for symbolic participation. Contemporary psychotherapeutic approaches partially address this challenge, yet they either reproduce modernist assumptions about a coherent self or employ postmodern deconstruction as a therapeutic strategy. Perform-therapy, grounded in Raoul Eshelman’s theory of performatism, is proposed as a new psychotherapeutic paradigm capable of restoring existential engagement without resorting to naive idealism.